The protective effect of Mucuna pruriens seeds against snake venom poisoning - Tan, N.H.; Fung, S.Y.; Sim, S.M.; Marinello, E.; Guerranti, R.; Aguiyi, J.C. (Elsevier, 2009)
Ethnopharmacological relevance The seed, leaf and root of Mucuna pruriens have been used in traditional medicine for treatments of various diseases. In Nigeria, the seed is used as oral prophylactics for snakebite. Aim of the study To study the protective effects of Mucuna pruriens seed extract against the lethalities of various snake venoms. Materials and methods Rats were pre-treated with Mucuna pruriens seed extract and challenged with various snake venoms. The effectiveness of anti-Mucuna pruriens (anti-MPE) antibody to neutralize the lethalities of snake venoms was investigated by in vitro neutralization. Results In rats, MPE pre-treatment conferred effective protection against lethality of Naja sputatrix venom and moderate protection against Calloselasma rhodostoma venom. Indirect ELISA and immunoblotting studies showed that there were extensive cross-reactions between anti-MPE IgG and venoms from many different genera of poisonous snakes, suggesting the involvement of immunological neutralization in the protective effect of MPE pre-treatment against snake venom poisoning. In vitro neutralization experiments showed that the anti-MPE antibodies effectively neutralized the lethalities of Asiatic cobra (Naja) venoms, but were not very effective against other venoms tested. Conclusions The anti-MPE antibodies could be used in the antiserum therapy of Asiatic cobra (Naja) bites.